The Complexity of TET2 Functions in Pluripotency and Development - Garcia-Outeiral, Vera; de la Parte, Cristina; Fidalgo, Miguel; Guallar, Diana (Frontiers in Cell and Developmental Biology, 2021)
Ten-eleven translocation-2 (TET2) is a crucial driver of cell fate outcomes in a myriad of biological processes, including embryonic development and tissue homeostasis. TET2 catalyzes the demethylation of 5-methylcytosine on DNA for transcriptional regulation. New exciting research has provided evidence for TET2 catalytic activity in post-transcriptional regulation through RNA hydroxymethylation. Here we review the current understanding of TET2 functions on both DNA and RNA, and the influence of these chemical modifications in normal development and pluripotency contexts, highlighting TET2 versatility in influencing genome regulation and cellular phenotypes.